Expressing our Uniqueness to Create a Sustainable Way of Life - Dragotto, Elena DDV (European Journal of Sustainable Development, 2016)
In a society where points of reference and specific roles are also lacking in human relations, where self-expression is often confused with unattainable, false, alien and frustrating stereotypes, developing a personal growth process that leads one to recognize one’s Uniqueness, allows one to build more intimate and satisfying relationships with oneself and with others. The result is the development of a society in which everyone perceives their own value, regardless of fashions and external models, and everyone is aware of their role and responsibilities, contributing with their Uniqueness to the development of their own complexity and richness. The approach of Voice Dialogue Counseling, created in the 70’s by psychologists and psychotherapists Hal and Sidra Stone, has proven to be very effective in helping people to discover and develop their own Uniqueness. With great respect for everyone’s human experience, Voice Dialogue Counseling aids people in expanding themselves, embracing more and more of their richness and complexity, without any judgment. Supporting human Uniqueness means safeguarding a valuable resource and making it available for the development of Humanity and the planet. Key words: Uniqueness, counseling, Voice Dialogue, Psychology of Selves, human relations, personal growth, Gross National Happiness